2013
DOI: 10.1007/s11010-013-1695-6
|View full text |Cite
|
Sign up to set email alerts
|

Sorafenib sensitizes hepatocellular carcinoma cell to cisplatin via suppression of Wnt/β-catenin signaling

Abstract: Hepatocellular carcinoma (HCC) is one of the most common cancers worldwide. Systemic chemotherapy plays an important role in the treatment of patients with advanced liver cancer. However, chemoresistance to cisplatin is a major limitation of cisplatin-based chemotherapy in the clinic, and the underlying mechanism of such resistance is not fully understood. In this study, we found that nuclear accumulation of β-catenin was higher in cisplatin-resistant Huh7 cells than in Huh7 cells, indicating that Wnt signalin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 20 publications
1
28
0
Order By: Relevance
“…Using the β-catenin inhibitor ICG001 combined with sorafenib we observed a relevantly decreased lC 50 in pHCC cells. This is in line with the interaction between activation of ERK and activity of β-catenin [24], and the inhibition of the wnt/β-catenin pathway by sorafenib [21]. Additional inhibition of β-catenin activity at the formation of transcription complex might also block the activation through tyrosine kinase signaling and enhance the effect of sorafenib in pediatric HCC, a tumor, in which β-catenin is often mutated and constitutively active.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Using the β-catenin inhibitor ICG001 combined with sorafenib we observed a relevantly decreased lC 50 in pHCC cells. This is in line with the interaction between activation of ERK and activity of β-catenin [24], and the inhibition of the wnt/β-catenin pathway by sorafenib [21]. Additional inhibition of β-catenin activity at the formation of transcription complex might also block the activation through tyrosine kinase signaling and enhance the effect of sorafenib in pediatric HCC, a tumor, in which β-catenin is often mutated and constitutively active.…”
Section: Discussionsupporting
confidence: 65%
“…In contrast to adult HCC [21], sorafenib did not reduce β-catenin expression in HC-AFW1 cells ( Supplemental Fig. 3).…”
Section: Sensitization Of Hc-afw1 Cells To Sorafenibmentioning
confidence: 87%
See 1 more Smart Citation
“…accumulating evidence has shown that CDDP in combination with other drugs, such as methotrexate and pemetrexed, significantly inhibited OS cells growth in vitro and in vivo (29,30). Of note, the synergistic anti-proliferative and pro-apoptotic effects of SOR in combination with CDDP were confirmed in human liver and gastric cancer cells (18,31). although SOR and CDDP alone or in combination have been found to inhibit other types of tumor growth, the effect on OS of SOR in combination CDDP has, to the best of our knowledge, yet to be reported.…”
Section: Discussionmentioning
confidence: 94%
“…Survivin is an anti-apoptotic molecule widely expressed in HCC. Overexpression of survivin leads to antiapoptosis (20). In this study, SL1122-37 was observed to have a greater activity than sorafenib in modulation of this pathway, suggesting its roles in the inhibition of HCC.…”
Section: Discussionmentioning
confidence: 53%